Mi colegio de Luis Antonio de Villena y la inminencia de la injuria - Coto-Rivel, Sergio (2015)
This article focuses on the intimate writing of the Spanish author Luis Antonio de Villena, particularly on his memoir book Mi colegio, published in 2006. This way, the article is built from two basic questions: first, which are the discursive strategies that characterize the memoir writing in the selected text? And second, in what way the insult as a discursive act is presented as a conductive thread in the memoir writing of the author? The answers to these questions will be developed from the textual analysis of Mi colegio, the comparison with other autobiographical texts of the author and the support of a series of theoretical elements that base our hypothesis.